2009
DOI: 10.1016/j.jneuroling.2008.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Argument structure effects in action verb naming in static and dynamic conditions

Abstract: Argument structure, as in the participant roles entailed within the lexical representation of verbs, affects verb processing. Recent neuroimaging studies show that when verbs are heard or read, the posterior temporoparietal region shows increased activation for verbs with greater versus lesser argument structure complexity, usually bilaterally. In addition, patients with agrammatic aphasia show verb production deficits, graded based on argument structure complexity. In the present study, we used fMRI to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
68
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 50 publications
12
68
2
3
Order By: Relevance
“…This hypothesis is silent on the specific direction of the effect: It does not speak to why neural activity increased for intransitive relative to transitive verbs (see also Assadollahi et al, 2009;den Ouden et al, 2009;Assadollahi & Rockstroh, 2008). Nonetheless, as argued in the Introduction, the correlation between transitivity and neural activity may be tentatively interpreted in terms of verb prototypicality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis is silent on the specific direction of the effect: It does not speak to why neural activity increased for intransitive relative to transitive verbs (see also Assadollahi et al, 2009;den Ouden et al, 2009;Assadollahi & Rockstroh, 2008). Nonetheless, as argued in the Introduction, the correlation between transitivity and neural activity may be tentatively interpreted in terms of verb prototypicality.…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, Meltzer-Asscher, Schuchard, den Ouden, and Thomphon (2013) observed greater neural activity in the bilateral angular and supramarginal gyri, as well as in the right posterior superior temporal gyrus (STG), the right MTG, and the right middle and superior frontal gyri for verbs that can act as transitive or intransitive versus verbs that must exclusively act as intransitive. However, in an fMRI study using an overt action picture naming task (den Ouden et al, 2009), they found a wide range of regions that respond differentially to intransitive and transitive verbs, in both directions: transitive > intransitive and intransitive > transitive. Larger intransitive relative to transitive verb effects were reported for the right hemisphere in the thalamus, precentral gyrus, and STS (encompassing Heschlʼs gyrus and insula) and for left hemisphere in STG extending into Heschlʼs gyrus; larger transitive relative to intransitive verbs were reported in bilateral fusiform gyrus, middle occipital gyrus (extending into inferior occipital gyrus in the left hemisphere), pMTG and angular and supramarginal gyri, and the precuneus, as well as left hemisphere activation in the postcentral and precentral gyri, middle frontal gyrus (MFG), and infIFG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain imaging investigations of the neural network underlying the processing of verb argument structure have highlighted not only the role of anterior language areas (i.e. the inferior frontal gyrus), but have also put forward the decisive role played by the parietal cortex, and especially the angular gyrus [115,116].…”
Section: Action Recognition Imitation and Gestural Communication In mentioning
confidence: 99%
“…20 Asimismo, diversos estudios con pacientes adultos con afasia de Broca han mostrado que la producción de verbos se dificulta en relación con el número de argumentos que requiere cada verbo. 49 Baron, Erickson, Ahronovich, Baker y Litman 50 encontraron que en niños de tres años de edad nacidos con bajo peso y pretérmino (<26 semanas de gestación), el desempeño de la fluidez verbal se ubicó por debajo del grupo control (nacidos a término y con un peso "normal"); en otros estudios con grupos similares se ha encontrado replicación de estos resultados, por lo que se ha sugerido que la fluidez de verbos puede ser un predictor temprano de disfunción ejecutiva/dificultades de fluidez de lenguaje durante la infancia.…”
Section: Aplicación Clínicaunclassified